Prevalence and Measures for Curbing Ponzi Schemes in Public Tertiary Institutions in Nigeria - Christopher Chimaobi Ibekwe (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
The Nigerian business space is witnessing an upsurge in unregulated investment proposals that are promising unreasonable returns on investment. This paper examined prevalence and measures for curbing Ponzi schemes in Public tertiary institutions in Nigeria. Rationale choice theory, and mixed methods research design were employed. The study population was sixty-eight thousand, three hundred and fifty (68,350), while the sample size was one thousand and ninety-three (1,093) undergraduates. Multi-stage and purposive sampling techniques were used in selecting study participants. Data were generated using structured questionnaire and in-depth interviews (IDI) guide. Through the aid of SPSS quantitative data were processed and analysed using frequency distribution, percentages, graphic illustration and chi-square (x2) inferential statistics, while qualitative data were analyzed thematically. The findings revealed that undergraduates involve in Ponzi schemes and greater proportion of them have had up to 5 years of involvement. The study also showed that between 50% to 70% of the students had invested in a Ponzi scheme. It again indicated that money they invested in Ponzi schemes was very much. This paper concludes that there is prevalence of Ponzi schemes in public tertiary institutions, and that undergraduates spent significant part of their academic years gambling in those schemes. Therefore, it recommended amongst others that, financial crimes monitoring commissions and agencies in the country should intensify their efforts in the fight against fraud by deploying technology in tracking and clamping down Ponzi schemes once they are floated. This approach will give them no chance to spread to the public domain.